PEMBERDAYAAN MASYARAKAT MELALUI PENINGKATAN KUALITAS BIBIT TANAMAN BUAH DENGAN METODE MINI GRAFTING - Susiyanti, Susiyanti; Nurmayulis, Nurmayulis; Mulyati, Sri; Sjaifuddin, Sjaifuddin; Eris, Fitria Riany (Universitas Sultan Ageng Tirtayasa, 2019)
Fruit plants are commodities that can improve people's lives in the long term. One of the problemsin the cultivation of fruit trees is the provision of quality seedlings. Based on these considerations,community service has been carried out under the title